Virulence and Pathogenicity Properties of Aggregatibacter actinomycetemcomitans - Belibasakis GN; Maula T; Bao K; Lindholm M; Bostanci N; Oscarsson J; Ihalin R; Johansson A (MDPI, 2022)
Aggregatibacter actinomycetemcomitans is a periodontal pathogen colonizing the oral cavity of a large proportion of the human population. It is equipped with several potent virulence factors that can cause cell death and induce or evade inflammation. Because of the large genetic diversity within the species, both harmless and highly virulent genotypes of the bacterium have emerged. The oral condition and age, as well as the geographic origin of the individual, influence the risk to be colonized by a virulent genotype of the bacterium. In the present review, the virulence and pathogenicity properties of A. actinomycetemcomitans will be addressed.